Event Study: Pengaruh (PP) Nomor 10 Tahun 2025 Terhadap Reaksi Pasar Saham - Ningtyas, Fatmala Yulia Putri Utami (MDP Student Conference, 2025)
The inauguration of policy (PP) Number 10 of 2025 concerning the Establishment of BPI Danantara in the management of BUMN company investments. The research approach is quantitative event study method with an observation period of 10 days, namely 5 days before and after the inauguration of the policy through the research variables of abnormal return and trading volume activity. The selection of samples from secondary data of 36 BUMN companies with purposive sampling techniques was obtained from the official website of the Indonesia Stock Exchange (IDX). The normality test uses the Kolmogorov-Smirnov test and parametric hypothesis testing (Paired t-test). The results of the hypothesis test show that there is no significant difference in abnormal return and trading volume activity before and after the inauguration of the policy. This is the influence of negative information related to investor concerns in the management of BUMN company investments has not occurred